Reduced tibial strain-shielding with extraosseous total knee arthroplasty revision system - Correa,T; Pal,B; van,Arkel R; Vanacore,F; Amis,AA (Medical Engineering and Physics, 2018)
BackgroundRevision total knee arthroplasty (RTKA) has poorer results than primary total knee arthroplasty (TKA), and the prostheses are invasive and cause strain-shielding of the bones near the knee. This paper describes an RTKA system with extracortical fixation. It was hypothesised that this would reduce strain-shielding compared with intramedullary fixation.MethodsTwelve replica tibiae were prepared for full-field optical surface strain analysis. They were either left intact, implanted with RTKA components with cemented intramedullary fixation stems, or implanted with a novel design with a tibial tray subframe supported by two extracortical fixation plates and screw fixation. They were loaded to simulate peak walking and stair climbing loads and the surface strains were measured using digital image correlation. The measurements were validated with strain gauge rosettes.ResultsCompared to the intact bone model, extracortical fixation reduced surface strain-shielding by half versus intramedullary fixation. For all load cases and bone regions examined, the extracortical implant shielded 8–27% of bone strain, whereas the intramedullary component shielded 37–56%.ConclusionsThe new fixation design, which offers less bone destruction than conventional RTKA, also reduced strain-shielding. Clinically, this design may allow greater rebuilding of bone loss, and should increase long-term fixation.